2006
DOI: 10.1007/s11099-006-0032-7
|View full text |Cite
|
Sign up to set email alerts
|

Low concentrations of NaHSO<sub>3</sub> increase photosynthesis, biomass, and attenuate photoinhibition in Satsuma mandarin (Citrus unshiu Marc.) plants

Abstract: Spraying low concentrated (0.5-5.0 mM) solutions of NaHSO 3 on Satsuma mandarin (Citrus unshiu Marc.) leaves resulted in enhancement (maximal about 15 % at 1 mM NaHSO 3 ) of net photosynthetic rate (P N ) for 6 d. The potential photochemical efficiency of photosystem 2 (PS2, F v /F m ) and the quantum yield of PS2 electron transport (Φ PS2 ) were increased under strong photon flux density (PFD). The slow phase of millisecond delayed light emission (ms-DLE) was increased, showing that the transmembrane proton m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The treatments significantly enhanced net photosynthetic rate (P N ), carboxylation efficiency (CE), and the maximum response of P N to intercellular CO 2 concentration. The enhancement of P N by foliar application of low concentrations of bisulfite was due to increasing CE relevant to ribulose-1,5-bisphosphate (RuBP) carboxylase/oxygenase activity and regeneration rate of RuBP depending on ATP formation.Additional key words: chlorophyll fluorescence; intercellular CO 2 concentration; Melaleuca; photorespiration; photosystem 2; regeneration of ribulose-1,5-bisphosphate; stomatal conductance.--Low concentration of bisulfite has often been used for enhancing photosynthesis to promote field crop yield (Wang et al 2003, Chen et al 2005, Guo et al 2006. However, it is still unknown how it directly enhances carbon assimilation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The treatments significantly enhanced net photosynthetic rate (P N ), carboxylation efficiency (CE), and the maximum response of P N to intercellular CO 2 concentration. The enhancement of P N by foliar application of low concentrations of bisulfite was due to increasing CE relevant to ribulose-1,5-bisphosphate (RuBP) carboxylase/oxygenase activity and regeneration rate of RuBP depending on ATP formation.Additional key words: chlorophyll fluorescence; intercellular CO 2 concentration; Melaleuca; photorespiration; photosystem 2; regeneration of ribulose-1,5-bisphosphate; stomatal conductance.--Low concentration of bisulfite has often been used for enhancing photosynthesis to promote field crop yield (Wang et al 2003, Chen et al 2005, Guo et al 2006. However, it is still unknown how it directly enhances carbon assimilation.…”
mentioning
confidence: 99%
“…--Low concentration of bisulfite has often been used for enhancing photosynthesis to promote field crop yield (Wang et al 2003, Chen et al 2005, Guo et al 2006. However, it is still unknown how it directly enhances carbon assimilation.…”
mentioning
confidence: 99%
“…Treating leaves with low NaHSO 3 concentrations has often been used for enhancing photosynthesis to promote field crop yield Guo et al 2006). The effect of NaHSO 3 on plant growth, photosynthetic efficiency, and enzyme activity was demonstrated in this study.…”
Section: Discussionmentioning
confidence: 58%
“…Low concentration of bisulfite has often been used for enhancing photosynthesis to promote field crop yield (Guo et al 2006). Bisulfite (HSO 3 ), a physiological form of SO 2 , is generally detrimental to plant tissues (Zoran et al 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies showed that low concentrations of NaHSO 3 and INH could promote photosynthesis of plants, increase the yield and improve the product quality (Black and Unsworth 1979;Wang et al 2002;Guo et al 2006). After a NaHSO 3 solution was sprayed onto Hordeum vulgare Linn.…”
mentioning
confidence: 99%